Molecular pathology of lung cancer - Cagle, Philip T. (Molecular Pathology Library, 2012)
As with other books in the Molecular Pathology Library Series, Molecular Pathology of Lung Cancer bridges the gap between the molecular specialist and the clinical practitioner, including the surgical pathologist who now has a key role in decisions regarding molecular targeted therapy for lung cancer. Molecular Pathology of Lung Cancer provides the latest information and current insights into the molecular basis for lung cancer, including precursor and preinvasive lesions, molecular diagnosis, molecular targeted therapy, molecular prognosis, molecular radiology and related fields for lung cancer generally and for the specific cell types. As many fundamental concepts about lung cancer have undergone revision in only the past few years, this book will likely be the first to comprehensively cover the new molecular pathology of lung cancer. It provides a foundation in this field for pathologists, medical oncologists, radiation oncologists, thoracic surgeons, thoracic radiologists and their trainees, physician assistants, and nursing staff.